Implementasi Teknologi IoT Pada Smart Home - Ramdani, Febryan; Dhika, Harry (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2020)
Indonesia to date has implemented a variety of telecommunications technologies forImproving quality and improving quality so that improvements need to be done in all fields, one of them is Telecommunications Infrastructure. Internet of Things (IoT) technology, offering smart services and networks. But to implement IoT technology requires a lot of costs and is quite expensive, therefore it is necessary to formulate a strategy that is suitable for implementing IoT technology. To formulate a plan based on the concept of strategic management science using strategy formulation using a strategy process consisting of MEI (Evaluation Matrix Internal), MEE (External Evaluation Matrix), SWOT, External Internal Matrix, and Grand Strategy. After formulating it was found that the